2017
DOI: 10.1534/g3.116.035741
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-Sequencing-Based Investigation of the Genetic Architecture Responsible for a ∼Sevenfold Increase in Soybean Seed Stearic Acid

Abstract: Soybean oil is highly unsaturated but oxidatively unstable, rendering it nonideal for food applications. Until recently, the majority of soybean oil underwent partial chemical hydrogenation, which produces trans fats as an unavoidable consequence. Dietary intake of trans fats and most saturated fats are conclusively linked to negative impacts on cholesterol levels and cardiovascular health. Two major soybean oil breeding targets are: (1) to reduce or eliminate the need for chemical hydrogenation, and (2) to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Recent research has demonstrated large effects on nodule development when seed stearic acid levels are altered, so achieving the threshold in soybeans without ultimately sacrificing yield may be problematic (Gillman et al, ; Lakhssassi et al, ). The two major quantitative trait loci besides the null allele of SACPD‐C contributing to greater than 20% stearic acid levels from soybean breeding line A6 have not yet been evaluated in a high oleic acid background (Heim & Gillman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated large effects on nodule development when seed stearic acid levels are altered, so achieving the threshold in soybeans without ultimately sacrificing yield may be problematic (Gillman et al, ; Lakhssassi et al, ). The two major quantitative trait loci besides the null allele of SACPD‐C contributing to greater than 20% stearic acid levels from soybean breeding line A6 have not yet been evaluated in a high oleic acid background (Heim & Gillman, ).…”
Section: Discussionmentioning
confidence: 99%
“…The successful implementation of GBS, however, require proper library construction and sequence analyses, and benefit from a good reference genome for analysis. For these reasons, GBS has been most widely used for plant research programs in the most important crops like wheat ( Lin et al, 2015 ), rice ( Spindel et al, 2013 ), maize ( Romay et al, 2013 ), and soybean ( Heim and Gillman, 2017 ). In this study, we applied GBS to a group of pseudocereals and orphan crop jointly termed the grain amaranths whose reference genome has only recently been prepared ( Clouse et al, 2016 ; Lightfoot et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the small size of the Amaranthus genome (∼500 Mb), we used the restriction enzyme indicated for GBS genome complexity reduction that has been used in rice ( De Leon et al, 2016 ), another small genome species. This same enzyme has functioned well for GBS in maize ( Ertiro et al, 2015 ) and soybean ( Heim and Gillman, 2017 ) with larger genomes. Size selection using magnetic beads after digestion and ligation with adapters was for DNA fragments of approximately 300 bp ( Rohland and Reich, 2012 ).…”
Section: Methodsmentioning
confidence: 96%
“…The use of GBS for cultivated soybean has focused on crop improvement through genomic selection and quantitative trait mapping (Sonah et al, 2013;Bastien et al, 2014;Jarqu ın et al, 2014;Sonah et al, 2015;Zhou et al, 2015;Torkamaneh et al, 2016;Heim & Gillman, 2017). These studies provided us with information about a suitable restriction enzyme, ApeK1, and an estimate of the number of restrictions sites it would generate in the genomes of congeneric soybean relatives with similar sized genomes (over 675 000 sites; Fig.…”
Section: Gbs In the Soybean Genusmentioning
confidence: 99%